answersLogoWhite

0


Best Answer

Given,

4x2 - 4x + 3 = 0; then,

4x2 - 4x + 1 = (2x - 1)2 = -2,

2x - 1 = √-2 = ±i√2, and

2x = 1 ± i√2;

therefore,

x = ½(1 ± i√2).

User Avatar

Wiki User

โˆ™ 2010-07-01 03:19:38
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.74
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1200 Reviews

Add your answer:

Earn +20 pts
Q: 4x x to second power - 4x plus 3 equals 0?
Write your answer...
Submit
Still have questions?
magnify glass
imp
People also asked